Clinical and safety outcomes in unresectable, very early and early-stage hepatocellular carcinoma following Irreversible Electroporation (IRE) and Transarterial Chemoembolization (TACE): A systematic literature review and meta-analysis - Kristen A. Cribbs; Wesley T. Baisley; Betsy J. Lahue; Praveen Peddu (PLoS ONE, 2025)
Background Locoregional treatments for early-stage unresectable hepatocellular carcinoma (HCC) are widely used, with irreversible electroporation (IRE) and transarterial chemoembolization (TACE) representing two non-thermal treatment options. However, to date, no systematic evaluations of these technologies have been conducted. This study sought to comparatively assess the safety and effectiveness of IRE and TACE for the treatment of very early and early-stage, inoperable HCC via systematic literature reviews (SLRs) and meta-analyses. Methodology Searches were conducted targeting English-language publications and congress proceedings of clinical trials and observational studies from January 1, 2012 to December 21, 2023 that reported effectiveness and safety outcomes (tumor response, progression-free survival (PFS), adverse events (AE)) for IRE and TACE. Two reviewers independently assessed eligibility and abstracted data. For each procedure, meta-analyses were conducted to assess tumor response by follow-up time point, as data permitted, and other outcomes were descriptively analyzed; Quality and risk of bias assessments were performed. Results 12 IRE publications (195 patients) and 33 TACE publications (6,899 patients) met eligibility criteria. During 0 to < 3 month follow-up, complete response was achieved in 84% of IRE patients vs. 68% for TACE (all results at 1-month); a proportion that increased at 3 to < 6 months (91% IRE vs. 41% TACE). Median PFS was 10.4 months for IRE and 19–30 months for TACE. Serious AEs (SAEs) were experienced by 4% vs. 5% of IRE and TACE patients, respectively. Conclusion Both IRE and TACE are safe and effective non-thermal treatments for unresectable, very early and early-stage HCC. The high rate of short-term complete response observed for IRE, coupled with a low SAE rate, may support the broader adoption of this procedure in this patient population.